2018
DOI: 10.1021/jacs.7b11968
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Origin of the Regioselectivity in Cyclopolymerizations of Diynes and How to Completely Switch It

Abstract: Grubbs-type olefin metathesis catalysts are known to cyclopolymerize 1,6-heptadiynes to afford conjugated polyenes containing five- or six-membered carbocycles. Although high levels of regioselectivity up to >99:1 were observed previously for the formation of five-membered rings, it was neither possible to deliberately obtain six-membered rings at similar levels of selectivity nor understood why certain catalysts showed this selectively. Combining experimental and computational methods, a novel and general the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

6
4

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 49 publications
1
23
0
Order By: Relevance
“…Cyclopolymerization (CP) of α,ω -diyne derivatives is a powerful tool for preparing substituted polyacetylenes. Early studies regarding CP used ill-defined catalysts, including Ziegler–Natta, MoCl 5 , and WCl 6 catalysts, until the first breakthrough by the Schrock group and later by the Buchmeiser group demonstrating living CP using well-defined Mo-based olefin metathesis catalysts. Subsequently, the utility of CP broadened when user-friendly Ru-based catalysts were shown to promote living CP. Extensive studies have been conducted using 1,6-heptadiyne monomers, yielding five- or six-membered rings (in a random or highly regioselective fashion) in the conjugated backbone via α - , or β -addition, , respectively. Moreoever, recent studies have expanded the scope of CP where 1,7-octadiyne and 1,8-nonadiyne derivatives were used to successfully produce polyacetylenes containing six- and seven-membered rings via α -addition (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…Cyclopolymerization (CP) of α,ω -diyne derivatives is a powerful tool for preparing substituted polyacetylenes. Early studies regarding CP used ill-defined catalysts, including Ziegler–Natta, MoCl 5 , and WCl 6 catalysts, until the first breakthrough by the Schrock group and later by the Buchmeiser group demonstrating living CP using well-defined Mo-based olefin metathesis catalysts. Subsequently, the utility of CP broadened when user-friendly Ru-based catalysts were shown to promote living CP. Extensive studies have been conducted using 1,6-heptadiyne monomers, yielding five- or six-membered rings (in a random or highly regioselective fashion) in the conjugated backbone via α - , or β -addition, , respectively. Moreoever, recent studies have expanded the scope of CP where 1,7-octadiyne and 1,8-nonadiyne derivatives were used to successfully produce polyacetylenes containing six- and seven-membered rings via α -addition (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…However, these new polymers showed lower optical band-gaps than the five-membered analogues, thereby making them potentially more attractive materials in the electronic application 42. We also examined the origin of the exceptional regioselectivity using DFT calculations, concluding that Ru1 which had adopted trigonal bipyramidal geometry would prefer β-addition due to electronic effects 43. However, both catalysts showed very slow initiation rate ( k i ) and relatively fast propagation rate ( k p ) leading to low k i / k p values and poor MW control.…”
Section: Introductionmentioning
confidence: 99%
“…[57] Furthermore, GC and TOF-MS monitoring of the metathesis of diethyl diallylmalonate and allylmethallylmalonate with a series of NHC-based Ru catalysts indicated that non-productive cross metathesis (CM) can be competitive with ring-closing metathesis, [58] and that less hindered NHC ligands are more prone to undergo non-productive (2,1) CM. These findings highlight the relevance of understanding the factors controlling the regioselectivity of the metathesis event, [59] as in the formation of di-J o u r n a l P r e -p r o o f and tri-substituted olefins most of the catalytic turnover events occur in non-productive metathesis that regenerates only the metathesis partners, but not the desired, productive cross metathesis products. [60] Scheme 2.…”
Section:  Introductionmentioning
confidence: 91%